Abnormal Right Ventricular Myocardial Performance Index Is Not Associated With Outcomes in Invasively Ventilated Intensive Care Unit Patients Without Acute Respiratory Distress Syndrome—Post hoc Analysis of Two RCTs - Pierrakos, Charalampos; Geke Algera, Anna; Simonis, Fabienne; Cherpanath, Thomas G. V.; Lagrand, Wim K.; Paulus, Frederique; Bos, Lieuwe D. J.; Schultz, Marcus J.; , the PReVENT– and RELAx–Investigators (Frontiers in Cardiovascular Medicine, 2022)
Background The objective of the study was to determine the association between right ventricular (RV) myocardial performance index (MPI) and successful liberation from the ventilator and death within 28 days. Methods Posthoc analysis of 2 ventilation studies in invasively ventilated patients not having ARDS. RV–MPI was collected through transthoracic echocardiography within 24 to 48 hours from start of invasive ventilation according to the study protocols. RV–MPI ≤ 0.54 was considered normal. The primary endpoint was successful liberation from the ventilator < 28 days; the secondary endpoint was 28–day mortality. Results 81 patients underwent transthoracic echocardiography at median 30 (24–42) hours after start of ventilation––in 73 (90%) patients the RV–MPI could be collected. 56 (77%) patients were successfully liberated from the ventilator < 28 days; 22 (30%) patients had died before or at day 28. 18 (25%) patients had an abnormal RV–MPI. RV–MPI was neither associated with successful liberation from the ventilator within 28 days (HR, 2.2 [95%–CI 0.47–10.6]; P = 0.31) nor with 28–day mortality (HR, 1.56 [95% CI 0.07–34.27]; P=0.78). Conclusions In invasively ventilated critically ill patients without ARDS, an abnormal RV–MPI indicative of RV dysfunction was not associated with time to liberation from invasive ventilation.